"c.2,v.4" - Gokhale Institute of Politics and Economics (Bombay, 1981)
This is the fourth and the last volume in the series of Selected Writings and speeches of professor D.R. Gadgil. The earlier volume in the series are planning and Economic policy in India (1972), Writings and Speeches of professor D.R. Gadgil on planning and Developments : 19676-1971 (1973) and writing and Speeches of professor D.R. Gadgil on Cooperation (1975). The Material that was not included in the above three volumes was wide -ranging in the coverage of the subjects of discourse as well as in time.
Keywords: "Gadgil, D R"